A positive electrode active material for sodium ion battery and its preparation method and application

By doping layered oxide positive electrode active materials with fluorine doping a variety of filtered metal elements and fluorine elements, the problem of easy moisture absorption of existing materials is solved, significantly improving the material's hygroscopicity and circulation performance, and improving the overall performance of sodium ion batteries.

CN115224269BActive Publication Date: 2025-04-04SHANGHAI LING FRANCIUM NEW ENERGY TECH CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202210713082.9
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-06-22
Publication Date
2025-04-04
Estimated Expiration
2042-06-22

AI Technical Summary

Technical Problem

The existing layered oxide positive electrode active materials are prone to moisture absorption and have many side reactions, which affects the electrochemical performance of sodium ion batteries.

Method used

A variety of filtered metal elements (such as iron, nickel, manganese, titanium, chromium) are mixed and doped with fluorine elements to form a specific layered oxide structure to improve hygroscopic resistance and electrochemical properties.

Benefits of technology

It significantly improves the hygroscopicity and circulation performance of the positive electrode active material, reduces the pulping complexity, and improves the energy density and stability of sodium ion batteries.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN115224269B_ABST
    Figure CN115224269B_ABST
Patent Text Reader

Abstract

The present invention provides a positive electrode active material for a sodium ion battery and a preparation method and application thereof. The molecular formula of the positive electrode active material is Na a Fe 1‑x‑y‑z‑v Ni x Mn y Ti z Zr v O 2‑b F b , where a, x, y, z, v, b are molar fractions, 0.5≤a≤1.0, 0.2≤x≤0.7, 0.2≤y≤0.7, 0.01≤z≤0.3, 0.01≤v≤0.3, 0.01≤b≤0.2. Compared with the prior art, the layered oxide positive electrode active material of the present invention mixes a variety of filtered metal elements and dopes F elements for substitution, thereby forming a unique structure, which has good anti-hygroscopicity and can well solve the problem of easy moisture absorption of the current layered oxide positive electrode active material; at the same time, the positive electrode active material of the structure also has excellent electrochemical properties, which can improve the cycle performance of sodium ion batteries.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of sodium batteries, and in particular to a positive electrode active material for sodium ion batteries, a preparation method thereof and an application thereof. Background Art

[0002] Lithium-ion batteries have excellent cycle performance and high energy density, and are widely used in new energy vehicles, large-scale energy storage, and smart terminal products. The rapidly growing market has led to a huge demand for lithium-ion batteries. While lithium-ion battery manufacturers have increased production on a large scale, the problem of lithium resource shortage has gradually emerged.

[0003] Compared with lithium resources, sodium resources, which are also alkali metals, are extremely abundant, cheap, and widely distributed. Sodium-based secondary batteries have the advantage of low cost. Therefore, the development of practical sodium-ion batteries is particularly important. The positive electrode active material of sodium-ion batteries is a key factor restricting the electrochemical performance of sodium-ion batteries. According to the characteristics of sodium-ion batteries, researchers have designed and developed a series of positive electrode active materials including sodium vanadium phosphate, Prussian blue, sodium manganate, and layered oxides. Among them, layered oxide positive electrode active materials have the advantages of high capacity and long cycle life, but at the same time, layered oxide positive electrode active materials are highly alkaline and have disadvantages such as easy moisture absorption and many side reactions.

[0004] In view of this, it is indeed necessary to provide a technical solution to the above problems. Summary of the invention

[0005] One of the purposes of the present invention is to provide a positive electrode active material for a sodium ion battery, which solves the shortcomings of the current layered oxide positive electrode active materials, such as easy moisture absorption and many side reactions.

[0006] In order to achieve the above object, the present invention adopts the following technical solutions:

[0007] A positive electrode active material for a sodium ion battery, the molecular formula of the positive electrode active material is Na a Fe 1-x-y-z- v Ni x Mn y Ti z Zr v O 2-b F b , where a, x, y, z, v, and b are mole fractions, 0.5≤a≤1.0, 0.2≤x≤0.7, 0.2≤y≤0.7, 0.01≤z≤0.3, 0.01≤v≤0.3, and 0.01≤b≤0.2.

[0008] The second object of the present invention is to provide a method for preparing the above-mentioned positive electrode active material for sodium ion battery, comprising the following steps:

[0009] S1. Weigh a sodium source compound, an iron source compound, a nickel source compound, a manganese source compound, a titanium source compound, a zirconium source compound, and a fluorine source compound according to a stoichiometric formula and premix them to obtain a premixed powder;

[0010] S2, adding the premixed powder, solvent and dispersant into a nano sand mill for ball milling to obtain a slurry, wherein the primary particle size of the slurry is in the range of 100 to 200 nm;

[0011] S3, spray drying and granulating the slurry to obtain a precursor; then sintering the precursor, cooling, and obtaining Na a Fe 1-x-y-z-v Ni x Mn y Ti z Zr v O 2-b F b Layered oxide positive electrode active materials.

[0012] Preferably, the sodium source compound includes one or more of sodium carbonate, sodium hydroxide, sodium oxalate and sodium nitrate; the iron source compound includes one or more of iron carbonate, iron oxide, iron nitrate and ferrous oxalate; the nickel source compound includes one or more of nickel nitrate, nickel carbonate, nickel oxalate and nickel oxide; the manganese source compound includes one or more of manganese nitrate, manganese carbonate, manganese oxalate and manganese oxide; the fluorine source compound is ammonium fluoride and / or fluoroethylene carbonate.

[0013] Preferably, the titanium source compound is nano titanium dioxide; the primary particle size of the nano titanium dioxide is 200-500 nm; the zirconium source compound is nano zirconium oxide; the primary particle size of the nano zirconium oxide is 200-500 nm.

[0014] Preferably, in step S2, the mass ratio of the premixed powder to the solvent is 1:(1-5); the mass of the dispersant is 0.1-2% of the mass of the solvent; and the ball milling time is 8-15 hours.

[0015] Preferably, the dispersant is any one of ammonium polyacrylate, polyvinyl pyrrolidone and polyethylene glycol; and the solvent is deionized water.

[0016] Preferably, in step S3, the inlet temperature of the spray dryer used for the spray drying is 200-250°C, and the outlet temperature is 100-120°C.

[0017] Preferably, in step S3, the sintering temperature is 700-1000° C., and the sintering time is 10-20 hours.

[0018] The third object of the present invention is to provide a positive electrode sheet, comprising a positive electrode current collector and a positive electrode active material layer coated on at least one surface of the positive electrode current collector, wherein the positive electrode active material layer comprises the positive electrode active material described above.

[0019] A fourth object of the present invention is to provide a sodium ion battery, comprising a positive electrode sheet, a negative electrode sheet and a separator separated between the positive electrode sheet and the negative electrode sheet, wherein the positive electrode sheet is the positive electrode sheet described above.

[0020] Preferably, the positive electrode sheet also includes a positive electrode sodium supplement material, and the molecular formula of the positive electrode sodium supplement material is Na c Fe 1-d-e-f Al d Ti e Mg f O2, where c, d, e, and f are mole fractions, 0.8≤c≤1.5, 0.05≤d≤0.3, 0.05≤e≤0.3, and 0.05≤f≤0.3.

[0021] Compared with the prior art, the present invention has the following beneficial effects:

[0022] 1) The layered oxide positive electrode active material provided by the present invention mixes a variety of filtered metal elements and dopes them with F elements for substitution, thereby forming a unique structure. The structure has good anti-hygroscopicity and can well solve the problem that the current layered oxide positive electrode active materials are easy to absorb moisture. At the same time, the positive electrode active material with this structure also has excellent electrochemical properties. The synergistic effect of multiple transition metal elements such as iron, nickel, manganese, titanium, and chromium can significantly improve the structural stability of the material, and the doped fluorine can further increase the bond energy between anions and cations, so that the positive electrode active material of the present invention has good structural stability and cycle performance.

[0023] 2) In addition, the positive electrode active material provided by the present invention is not easy to form gel during the pulping process, and the pulping process and coating process are simpler, which lays a solid foundation for the stable performance of the positive electrode sheet and has significant economic value.

[0024] 3) In addition, the sodium ion battery provided by the present invention also includes a positive electrode sodium supplement material, which has good compatibility with the positive electrode active material and can be better integrated into the positive electrode sheet, effectively reducing the capacity loss of the battery during the first charge and discharge process of the sodium ion battery, so as to further improve the energy density and cycle performance of the sodium ion battery. BRIEF DESCRIPTION OF THE DRAWINGS

[0025] Figure 1 1 is a cycle performance diagram of the sodium ion battery of Example 1 of the present invention and Comparative Example 1. DETAILED DESCRIPTION

[0026] 1. Cathode active materials for sodium ion batteries

[0027] The first aspect of the present invention is to provide a positive electrode active material for a sodium ion battery, the molecular formula of the positive electrode active material is Na a Fe 1-x-y-z-v Ni x Mn y Ti z Zr v O 2-b F b , where a, x, y, z, v, and b are mole fractions, 0.5≤a≤1.0, 0.2≤x≤0.7, 0.2≤y≤0.7, 0.01≤z≤0.3, 0.01≤v≤0.3, and 0.01≤b≤0.2.

[0028] Preferably, the positive electrode active material may be NaFe 0.3 Ni 0.3- Mn 0.3 Ti 0.05 Zr 0.05 O 1.98 F 0.02 、Na 0.9 Fe 0.4 Ni 0.2- Mn 0.2 Ti 0.1 Zr 0.1 O 1.95 F 0.05 、NaFe 0.05 Ni 0.6- Mn 0.2 Ti 0.1 Zr 0.05 O 1.9 F 0.1 、Na 0.5 Fe 0.1 Ni 0.2- Mn 0.6 Ti 0.05 Zr 0.05 O 1.8 F 0.2 .

[0029] The second aspect of the present invention is to provide a method for preparing the positive electrode active material for a sodium ion battery, comprising the following steps:

[0030] S1. Weigh a sodium source compound, an iron source compound, a nickel source compound, a manganese source compound, a titanium source compound, a zirconium source compound, and a fluorine source compound according to a stoichiometric formula and premix them to obtain a premixed powder; preferably, the premixing method is grinding;

[0031] S2, adding the premixed powder, solvent and dispersant into a nano sand mill for ball milling to obtain a slurry, wherein the primary particle size of the slurry is in the range of 100 to 200 nm;

[0032] S3, spray drying and granulating the slurry to obtain a precursor; then sintering the precursor, cooling, and obtaining Na a Fe 1-x-y-z-v Ni x Mn y Ti z Zr v O 2-b F b Layered oxide positive electrode active materials.

[0033] Preferably, the sodium source compound includes one or more of sodium carbonate, sodium hydroxide, sodium oxalate and sodium nitrate; the iron source compound includes one or more of iron carbonate, iron oxide, iron nitrate and ferrous oxalate; the nickel source compound includes one or more of nickel nitrate, nickel carbonate, nickel oxalate and nickel oxide; the manganese source compound includes one or more of manganese nitrate, manganese carbonate, manganese oxalate and manganese oxide; the fluorine source compound is ammonium fluoride and / or fluoroethylene carbonate.

[0034] Preferably, the titanium source compound is nano titanium dioxide; the primary particle size of the nano titanium dioxide is 200-500nm; the zirconium source compound is nano zirconium oxide; the primary particle size of the nano zirconium oxide is 200-500nm. More preferably, the primary particle size of nano titanium dioxide is 300nm; the primary particle size of nano zirconium oxide is 300nm. Titanium and zirconium are both prepared as positive electrode active materials using nano-scale raw materials, which can be better pre-mixed with sodium source, iron source, nickel source, manganese source and fluorine source to obtain a purer positive electrode active material.

[0035] Preferably, in step S2, the mass ratio of the premixed powder to the solvent is 1:(1-5); the mass of the dispersant is 0.1-2% of the mass of the solvent; and the ball milling time is 8-15 hours. Preferably, the mass ratio of the premixed powder to the solvent is 1:2; the mass of the dispersant is 1% of the mass of the solvent; and the ball milling time is 10 hours.

[0036] Preferably, the dispersant is any one of ammonium polyacrylate, polyvinyl pyrrolidone and polyethylene glycol; and the solvent is deionized water. More preferably, the dispersant is ammonium polyacrylate.

[0037] Preferably, in step S3, the inlet temperature of the spray dryer used for the spray drying is 200-250°C, and the outlet temperature is 100-120°C. More preferably, the inlet temperature is 230°C, and the outlet temperature is 110°C. The slurry is sprayed and granulated at a temperature within the above range, which can obtain a precursor with more moderate particles and more uniform particle size distribution, so as to obtain a positive electrode active material with better performance.

[0038] Preferably, in step S3, the sintering temperature is 700-1000°C, and the sintering time is 10-20 hours. More preferably, the sintering temperature is 800°C, 850°C, 850°C, and the sintering time is 10 hours, 15 hours, or 20 hours.

[0039] Preferably, in step S3, the sintering atmosphere is an air atmosphere.

[0040] 2. Positive electrode

[0041] The third aspect of the present invention is to provide a positive electrode sheet, comprising a positive electrode current collector and a positive electrode active material layer coated on at least one surface of the positive electrode current collector, wherein the positive electrode active material layer comprises the positive electrode active material described above.

[0042] 3. Sodium-ion battery

[0043] A fourth aspect of the present invention is to provide a sodium ion battery, comprising a positive electrode sheet, a negative electrode sheet and a separator separated between the positive electrode sheet and the negative electrode sheet, wherein the positive electrode sheet is the positive electrode sheet described above.

[0044] Preferably, the positive electrode sheet also includes a positive electrode sodium supplement material, and the molecular formula of the positive electrode sodium supplement material is Na c Fe 1-d-e-f Al d Ti e Mg f O2, where c, d, e, and f are mole fractions, 0.8≤c≤1.5, 0.05≤d≤0.3, 0.05≤e≤0.3, and 0.05≤f≤0.3.

[0045] To make the technical solutions and advantages of the present invention more clear, the present invention and its beneficial effects will be described in further detail below in conjunction with specific implementation methods and accompanying drawings, but the implementation methods of the present invention are not limited thereto.

[0046] Example 1

[0047] A positive electrode active material for sodium ion batteries, with the molecular formula NaFe 0.3 Ni 0.3- Mn 0.3 Ti 0.05 Zr 0.05 O1.98 F 0.02 .

[0048] The preparation method of the positive electrode active material comprises the following steps:

[0049] S1. According to the stoichiometric formula, sodium carbonate, iron oxide, nickel carbonate, manganese carbonate, 300 nm titanium dioxide, 300 nm zirconium oxide and ammonium fluoride are weighed and ground and premixed to obtain a premixed powder; wherein the molar ratio of Na:Fe:Ni:Mn:Ti:Zr:F is 1:0.3:0.3:0.3:0.05:0.05:0.02;

[0050] S2, adding the premixed powder, deionized water and ammonium polyacrylate (ammonium polyacrylate is 1% of the mass of deionized water) in a mass ratio of 1:2 into a nano sand mill for high-energy ball milling for 10 hours to obtain a slurry, the primary particle size of which is about 100 nm;

[0051] S3, spray drying the slurry to obtain a precursor, the spray dryer inlet temperature is 230 ° C, the outlet temperature is 110 ° C; the precursor powder is sintered at 850 ° C for 15 hours in an air atmosphere, and naturally cooled to room temperature to obtain a precursor with a molecular formula of NaFe 0.3 Ni 0.3- Mn 0.3 Ti 0.05 Zr 0.05 O 1.98 F 0.02 Layered oxide cathode active materials for sodium-ion batteries.

[0052] The positive electrode active material obtained above is applied to positive electrode sheets and button batteries, and the preparation process is as follows:

[0053] Positive electrode sheet: 1.9 g of the obtained positive electrode active material was weighed, 0.05 g of carbon black and 0.05 g of polyvinylidene fluoride dissolved in N,N'-methylpyrrolidone were added, and the mixture was homogenized and coated on aluminum foil to prepare a positive electrode sheet.

[0054] Button cell: In a glove box with argon atmosphere, 2032 button cells were assembled with metallic sodium as the counter electrode, glass fiber as the separator, and 1M / NaPF6 / PC:EMC:EC (volume ratio 1:1:1) as the electrolyte.

[0055] Example 2

[0056] The difference from Example 1 is the preparation method of the positive electrode active material.

[0057] S3, spray drying the slurry to obtain a precursor, the spray dryer inlet temperature is 230 ° C, the outlet temperature is 180 ° C; the precursor powder is sintered at 850 ° C for 15 hours in an air atmosphere, and naturally cooled to room temperature to obtain a precursor with a molecular formula of NaFe 0.3 Ni 0.3- Mn 0.3 Ti 0.05 Zr 0.05 O 1.98 F 0.02 Layered oxide cathode active materials for sodium-ion batteries.

[0058] The rest is the same as in Example 1 and will not be described again here.

[0059] Example 3

[0060] The difference from Example 1 is the preparation method of the positive electrode active material.

[0061] S3, spray drying the slurry to obtain a precursor, the spray dryer inlet temperature is 150 ° C, the outlet temperature is 110 ° C; the precursor powder is sintered at 850 ° C for 15 hours in an air atmosphere, and naturally cooled to room temperature to obtain a precursor with a molecular formula of NaFe 0.3 Ni 0.3- Mn 0.3 Ti 0.05 Zr 0.05 O 1.98 F 0.02 Layered oxide cathode active materials for sodium-ion batteries.

[0062] The rest is the same as in Example 1 and will not be described again here.

[0063] Example 4

[0064] The difference from Example 1 is the content of each raw material of the positive electrode active material, wherein the molar ratio of Na:Fe:Ni:Mn:Ti:Zr:F is 0.9:0.4:0.2:0.2:0.1:0.1:0.05, and the molecular formula of the positive electrode active material for the obtained sodium ion battery is Na 0.9 Fe 0.4 Ni 0.2- Mn 0.2 Ti 0.1 Zr 0.1 O 1.95 F 0.05 .

[0065] The rest is the same as in Example 1 and will not be described again here.

[0066] Example 5

[0067] The difference from Example 1 is the content of each raw material of the positive electrode active material, wherein the molar ratio of Na:Fe:Ni:Mn:Ti:Zr:F is 1:0.05:0.6:0.2:0.1:0.05:0.1, and the molecular formula of the positive electrode active material for the obtained sodium ion battery is NaFe 0.05 Ni 0.6- Mn 0.2 Ti 0.1 Zr 0.05 O 1.9 F 0.1 .

[0068] The rest is the same as in Example 1 and will not be described again here.

[0069] Example 6

[0070] The difference from Example 1 is the content of each raw material of the positive electrode active material, wherein the molar ratio of Na:Fe:Ni:Mn:Ti:Zr:F is 0.5:0.1:0.2:0.6:0.05:0.05:0.2, and the molecular formula of the positive electrode active material for the obtained sodium ion battery is Na 0.5 Fe 0.1 Ni 0.2- Mn 0.6 Ti 0.05 Zr 0.05 O 1.8 F 0.2 .

[0071] The rest is the same as in Example 1 and will not be described again here.

[0072] Example 7

[0073] The preparation method of the positive electrode active material is different from that of Example 4.

[0074] The preparation method of the positive electrode active material comprises the following steps:

[0075] S1. According to the stoichiometric formula, sodium carbonate, iron oxide, nickel carbonate, manganese carbonate, 200 nm titanium dioxide, 200 nm zirconium oxide and ammonium fluoride are weighed and ground and premixed to obtain a premixed powder; wherein the molar ratio of Na:Fe:Ni:Mn:Ti:Zr:F is 0.9:0.4:0.2:0.2:0.1:0.1:0.05;

[0076] S2, adding the premixed powder, deionized water and ammonium polyacrylate (ammonium polyacrylate is 0.1% of the mass of deionized water) in a mass ratio of 1:5 into a nano sand mill for high-energy ball milling for 15 hours to obtain a slurry, the primary particle size of which is about 200 nm;

[0077] S3, spray drying the slurry to obtain a precursor, the spray dryer inlet temperature is 250 ° C, the outlet temperature is 100 ° C; the precursor powder is sintered at 1000 ° C for 10 hours in an air atmosphere, and naturally cooled to room temperature to obtain a precursor with a molecular formula of Na 0.9 Fe 0.4 Ni 0.2- Mn 0.2 Ti 0.1 Zr 0.1 O 1.95 F 0.05 Layered oxide cathode active materials for sodium-ion batteries.

[0078] The rest is the same as in Example 4 and will not be described again here.

[0079] Example 8

[0080] The preparation method of the positive electrode active material is different from that of Example 5.

[0081] The preparation method of the positive electrode active material comprises the following steps:

[0082] S1. According to the stoichiometric formula, sodium carbonate, iron oxide, nickel carbonate, manganese carbonate, 500 nm titanium dioxide, 500 nm zirconium oxide and ammonium fluoride are weighed and ground and premixed to obtain a premixed powder; wherein the molar ratio of Na:Fe:Ni:Mn:Ti:Zr:F is 1:0.05:0.6:0.2:0.1:0.05:0.1;

[0083] S2, the premixed powder, deionized water and ammonium polyacrylate (ammonium polyacrylate is 2% of the mass of deionized water) in a mass ratio of 1:1 are added to a nano sand mill for high-energy ball milling for 8 hours to obtain a slurry, the primary particle size of which is about 200 nm;

[0084] S3, spray drying the slurry to obtain a precursor, the spray dryer inlet temperature is 200 ° C, the outlet temperature is 120 ° C; the precursor powder is sintered at 900 ° C for 20 hours in an air atmosphere, and naturally cooled to room temperature to obtain a precursor with a molecular formula of NaFe 0.05 Ni 0.6- Mn 0.2 Ti 0.1 Zr 0.05 O 1.9 F 0.1 Layered oxide cathode active materials for sodium-ion batteries.

[0085] The rest is the same as in Example 5 and will not be described again here.

[0086] Example 9

[0087] The preparation method of the positive electrode active material is different from that of Example 6.

[0088] The preparation method of the positive electrode active material comprises the following steps:

[0089] S1. According to the stoichiometric formula, sodium carbonate, iron oxide, nickel carbonate, manganese carbonate, 200 nm titanium dioxide, 500 nm zirconium oxide and ammonium fluoride are weighed and ground and premixed to obtain a premixed powder; wherein the molar ratio of Na:Fe:Ni:Mn:Ti:Zr:F is 0.5:0.1:0.2:0.6:0.05:0.05:0.2;

[0090] S2, the premixed powder, deionized water and ammonium polyacrylate (ammonium polyacrylate is 0.5% of the mass of deionized water) in a mass ratio of 1:3 are added into a nano sand mill for high-energy ball milling for 14 hours to obtain a slurry, the primary particle size of which is about 200 nm;

[0091] S3, spray drying the slurry to obtain a precursor, the spray dryer inlet temperature is 240 ° C, the outlet temperature is 110 ° C; the precursor powder is sintered at 850 ° C for 20 hours in an air atmosphere, and naturally cooled to room temperature to obtain a precursor with a molecular formula of Na 0.5 Fe 0.1 Ni 0.2- Mn 0.6 Ti 0.05 Zr 0.05 O 1.8 F 0.2 Layered oxide cathode active materials for sodium-ion batteries.

[0092] The rest is the same as in Example 6 and will not be described again here.

[0093] Example 10

[0094] The difference from Example 9 is the preparation method of the positive electrode active material.

[0095] S3, spray drying the slurry to obtain a precursor, the spray dryer inlet temperature is 230 ° C, the outlet temperature is 180 ° C; the precursor powder is sintered at 850 ° C for 20 hours in an air atmosphere, and naturally cooled to room temperature to obtain a precursor with a molecular formula of Na 0.5 Fe 0.1 Ni 0.2- Mn 0.6 Ti 0.05 Zr 0.05 O 1.8 F 0.2 Layered oxide cathode active materials for sodium-ion batteries.

[0096] The rest is the same as in Example 9 and will not be described again here.

[0097] Embodiment 11

[0098] The difference from Example 9 is the preparation method of the positive electrode active material.

[0099] S3, spray drying the slurry to obtain a precursor, the spray dryer inlet temperature is 150 ° C, the outlet temperature is 110 ° C; the precursor powder is sintered at 850 ° C for 20 hours in an air atmosphere, and naturally cooled to room temperature to obtain a precursor with a molecular formula of Na 0.5 Fe 0.1 Ni 0.2- Mn 0.6 Ti 0.05 Zr 0.05 O 1.8 F 0.2 Layered oxide cathode active materials for sodium-ion batteries.

[0100] The rest is the same as in Example 9 and will not be described again here.

[0101] Example 12

[0102] The difference from Example 1 is the arrangement of the positive electrode sheet. The positive electrode sheet of this embodiment also contains a positive electrode sodium supplement material. The molecular formula of the positive electrode sodium supplement material is Na 1.1 Fe 0.7 Al 0.1 Ti 0.1 Mg 0.1 O2, the positive electrode sodium supplement material is mixed with 1.9g of positive electrode active material, 0.05g of carbon black and 0.05g of polyvinylidene fluoride dissolved in N,N'-methylpyrrolidone, and the mixture is homogenized and coated on aluminum foil to prepare a positive electrode sheet.

[0103] The rest is the same as in Example 1 and will not be described again here.

[0104] Example 13

[0105] The difference from Example 1 is the arrangement of the positive electrode sheet. The positive electrode sheet of this embodiment also contains a positive electrode sodium supplement material. The molecular formula of the positive electrode sodium supplement material is Na 1.3 Fe 0.7 Al 0.05 Ti 0.2 Mg 0.05 O2, the positive electrode sodium supplement material is mixed with 1.9g of positive electrode active material, 0.05g of carbon black and 0.05g of polyvinylidene fluoride dissolved in N,N'-methylpyrrolidone, and the mixture is homogenized and coated on aluminum foil to prepare a positive electrode sheet.

[0106] The rest is the same as in Example 1 and will not be described again here.

[0107] Embodiment 14

[0108] The difference from Example 2 is the arrangement of the positive electrode sheet. The positive electrode sheet of this embodiment also contains a positive electrode sodium supplement material. The molecular formula of the positive electrode sodium supplement material is Na1.1 Fe 0.7 Al 0.1 Ti 0.1 Mg 0.1 O2, the positive electrode sodium supplement material is mixed with 1.9g of positive electrode active material, 0.05g of carbon black and 0.05g of polyvinylidene fluoride dissolved in N,N'-methylpyrrolidone, and the mixture is homogenized and coated on aluminum foil to prepare a positive electrode sheet.

[0109] The rest is the same as in Example 2 and will not be described again here.

[0110] Embodiment 15

[0111] The difference from Example 4 is the arrangement of the positive electrode sheet. The positive electrode sheet of this embodiment also contains a positive electrode sodium supplement material. The molecular formula of the positive electrode sodium supplement material is Na 1.1 Fe 0.7 Al 0.1 Ti 0.1 Mg 0.1 O2, the positive electrode sodium supplement material is mixed with 1.9g of positive electrode active material, 0.05g of carbon black and 0.05g of polyvinylidene fluoride dissolved in N,N'-methylpyrrolidone, and the mixture is homogenized and coated on aluminum foil to prepare a positive electrode sheet.

[0112] The rest is the same as in Example 4 and will not be described again here.

[0113] Example 16

[0114] The difference from Example 6 is the arrangement of the positive electrode sheet. The positive electrode sheet of this embodiment also contains a positive electrode sodium supplement material. The molecular formula of the positive electrode sodium supplement material is Na 1.1 Fe 0.7 Al 0.1 Ti 0.1 Mg 0.1 O2, the positive electrode sodium supplement material is mixed with 1.9g of positive electrode active material, 0.05g of carbon black and 0.05g of polyvinylidene fluoride dissolved in N,N'-methylpyrrolidone, and the mixture is homogenized and coated on aluminum foil to prepare a positive electrode sheet.

[0115] The rest is the same as in Example 6 and will not be described again here.

[0116] Comparative Example 1

[0117] The difference from Example 1 is the arrangement of the positive electrode active material. The molecular formula of the positive electrode active material in this comparative example is NaFe 0.333 Ni 0.333- Mn 0.333 O2.

[0118] The rest is the same as in Example 1 and will not be described again here.

[0119] Comparative Example 2

[0120] The difference from Example 1 is the arrangement of the positive electrode active material. The molecular formula of the positive electrode active material in this comparative example is NaFe 0.3 Ni 0.3- Mn 0.3 Ti 0.05 Zr 0.05 O2.

[0121] The rest is the same as in Example 1 and will not be described again here.

[0122] Comparative Example 3

[0123] The difference from Example 1 is the arrangement of the positive electrode active material. The molecular formula of the positive electrode active material in this comparative example is NaFe 0.333 Ni 0.333 Mn 0.333 O 1.98 F 0.02 .

[0124] The rest is the same as in Example 1 and will not be described again here.

[0125] Comparative Example 4

[0126] The difference from Example 1 is the arrangement of the positive electrode active material. The molecular formula of the positive electrode active material in this comparative example is NaFe 0.3 Ni 0.3 Mn 0.3 Zr 0.1 O 1.98 F 0.02 .

[0127] The rest is the same as in Example 1 and will not be described again here.

[0128] The sodium ion batteries obtained in the above Examples 1 to 16 and Comparative Examples 1 to 4 were tested for cycle performance and anti-hygroscopicity performance.

[0129] Cycle performance: Cycle performance tests were performed on a Land battery tester with a test current of 0.1C and a test voltage range of 2.0-4.0V.

[0130] Anti-hygroscopicity: The positive electrode material was placed in a constant temperature and humidity chamber (25°C, humidity 50%) for 12 hours, then taken out and dried in a vacuum oven at 120°C for 12 hours, and then the button battery test was performed.

[0131] The test results are shown in Table 1.

[0132] Table 1

[0133]

[0134]

[0135] It can be seen from the test results of Examples 1 to 11 and Comparative Examples 1 to 4 in Table 1 above that when the layered oxide positive electrode active material consists of only iron, nickel and manganese transition metal ions, the positive electrode active material has the worst anti-hygroscopicity. After standing in constant temperature and humidity air, the positive electrode active material absorbs a large amount of moisture, resulting in enhanced alkalinity on the surface of the positive electrode active material, which in turn causes the binder PVDF to fail and form gel during the pulping process, making it impossible to effectively make positive electrode sheets, and the cycle performance of the positive electrode active material after standing deteriorates. When the transition metals are increased with Ti and Zr, the hygroscopicity of the positive electrode active material can be significantly suppressed, and the cycle performance can also be improved. The capacity retention rate after 50 cycles is increased to 82.4%, and the capacity retention rate will not decrease too much after 250 cycles. When the positive electrode material is further doped with fluorine ions, the effect on the material cycle performance is small when it is left standing in constant temperature and humidity air. In Example 1, the capacity retention rates after 50 cycles before and after constant temperature and humidity standing are 96.3% and 95.1%, respectively. The slurry state is good during the slurrying process, indicating that the synergistic effect of Ti, Zr, and F significantly improves the anti-hygroscopicity and cycle performance of the layered oxide.

[0136] In addition, it can be seen from the test results of Examples 12 to 16 and Examples 1 to 6 that when the positive electrode sodium supplement material of the present invention is further added to the positive electrode sheet, the positive electrode sodium supplement material has good compatibility with the positive electrode active material of the present invention, which can not only effectively supplement the sodium ions lost during the first cycle of the sodium ion battery, thereby effectively improving its subsequent cycle performance, but also maintain a good capacity retention rate after 250 cycles, and even after being placed at a constant temperature and humidity, it also maintains a relatively excellent performance in 250 cycles; at the same time, it also has a certain promoting effect on the anti-hygroscopic performance of the positive electrode active material, further improving the cycle performance of the battery. It can be seen that the positive electrode sodium supplement material provided by the present invention and the positive electrode active material of the present invention complement each other and can better improve the cycle performance of the sodium ion battery.

[0137] According to the disclosure and teaching of the above description, those skilled in the art to which the present invention belongs can also change and modify the above embodiment. Therefore, the present invention is not limited to the above specific embodiment, and any obvious improvement, replacement or modification made by those skilled in the art on the basis of the present invention belongs to the protection scope of the present invention. In addition, although some specific terms are used in this specification, these terms are only for the convenience of description and do not constitute any limitation to the present invention.

Claims

1. A positive electrode active material for a sodium ion battery, characterized in that: The molecular formula of the positive electrode active material is Na a Fe 1-x-y-z-v Ni x Mn y Ti z Zr v O 2-b F b , where a, x, y, z, v, and b are mole fractions, 0.5≤a≤1.0, 0.2≤x≤0.7, 0.2≤y≤0.7, 0.01≤z≤0.3, 0.01≤v≤0.3, and 0.01≤b≤0.

2.

2. A method for preparing a positive electrode active material for a sodium ion battery according to claim 1, characterized in that: The following steps are involved: S1. Weigh a sodium source compound, an iron source compound, a nickel source compound, a manganese source compound, a titanium source compound, a zirconium source compound, and a fluorine source compound according to a stoichiometric formula and premix them to obtain a premixed powder; S2, adding the premixed powder, solvent and dispersant into a nano sand mill for ball milling to obtain a slurry, wherein the primary particle size of the slurry is in the range of 100 to 200 nm; S3, spray drying and granulating the slurry to obtain a precursor; then sintering the precursor, cooling, and obtaining Na a Fe 1-x-y-z-v Ni x Mn y Ti z Zr v O 2-b F b Layered oxide positive electrode active materials.

3. The method for preparing a positive electrode active material for a sodium ion battery according to claim 2, characterized in that: The sodium source compound includes one or more of sodium carbonate, sodium hydroxide, sodium oxalate and sodium nitrate; the iron source compound includes one or more of iron carbonate, iron oxide, iron nitrate and ferrous oxalate; the nickel source compound includes one or more of nickel nitrate, nickel carbonate, nickel oxalate and nickel oxide; the manganese source compound includes one or more of manganese nitrate, manganese carbonate, manganese oxalate and manganese oxide; the fluorine source compound is ammonium fluoride and / or fluoroethylene carbonate.

4. The method for preparing a positive electrode active material for a sodium ion battery according to claim 2, characterized in that: The titanium source compound is nano titanium dioxide; the primary particle size of the nano titanium dioxide is 200-500nm; the zirconium source compound is nano zirconium oxide; the primary particle size of the nano zirconium oxide is 200-500nm.

5. The method for preparing a positive electrode active material for a sodium ion battery according to claim 2, characterized in that: In step S2, the mass ratio of the premixed powder to the solvent is 1:(1-5); the mass of the dispersant is 0.1-2% of the mass of the solvent; and the ball milling time is 8-15 hours.

6. The method for preparing a positive electrode active material for a sodium ion battery according to claim 5, characterized in that: The dispersant is any one of ammonium polyacrylate, polyvinyl pyrrolidone and polyethylene glycol; and the solvent is deionized water.

7. The method for preparing a positive electrode active material for a sodium ion battery according to claim 2, characterized in that: In step S3, the inlet temperature of the spray dryer used for the spray drying is 200-250°C, and the outlet temperature is 100-120°C.

8. A positive electrode sheet, comprising a positive electrode current collector and a positive electrode active material layer coated on at least one surface of the positive electrode current collector, characterized in that: The positive electrode active material layer includes the positive electrode active material according to claim 1 .

9. A sodium ion battery, comprising a positive electrode sheet, a negative electrode sheet and a separator between the positive electrode sheet and the negative electrode sheet, characterized in that: The positive electrode sheet is the positive electrode sheet according to claim 8.

10. The sodium ion battery according to claim 9, characterized in that: The positive electrode sheet also includes a positive electrode sodium supplement material, the molecular formula of which is Na c Fe 1-d-e-f Al d Ti e Mg f O2, where c, d, e, and f are mole fractions, 0.8≤c≤1.5, 0.05≤d≤0.3, 0.05≤e≤0.3, and 0.05≤f≤0.3.

Citation Information

Patent Citations

  • Sodium ion secondary battery, and layered titanate active substance, electrode material, anode and cathode adopted by the sodium ion secondary battery, and preparation method of the layered titanate active substance

    CN103456936A

  • Positive electrode active substance for sodium secondary cell, positive electrode for sodium secondary cell, and sodium secondary cell

    CN105103347A